Electrode composition, electrode slurry, electrode, and lithium secondary battery

CN122953544APending Publication Date: 2026-10-20LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580019479.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-25
Filing Date
2025-10-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,已知这种应用具有局限性,因为当包括橡胶基粘合剂时,硅基活性材料表现出差的分散性

Benefits of technology

[0026]当第二电极粘合剂溶解在电解质溶液中时,根据本发明的示例性实施方式的电极组合物可以降低电阻、改善输出和增强锂二次电池的寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to an electrode composition comprising: an electrode active material; and an electrode binder, wherein the electrode composition is a positive electrode composition or a negative electrode composition, and the electrode binder comprises a first electrode binder and a second electrode binder, wherein the first electrode binder is an insoluble binder insoluble in an electrolyte, and the second electrode binder is a soluble binder soluble in an electrolyte, wherein the second electrode binder is obtained by linking a polymer containing an electrolyte affinity functional group or a modified form of an electrolyte affinity functional group to the first electrode binder, and wherein the content of the second electrode binder relative to the electrode active material is 0.01 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrode compositions, electrode slurries, electrodes, and lithium secondary batteries.

[0002] Cross-references to related applications

[0003] This application claims priority and benefit to Korean Patent Application No. 10-2024-0147180, filed on October 25, 2024, with the Korean Intellectual Property Office, and Korean Patent Application No. 10-2025-0155274, filed on October 24, 2025, the entire contents of which are incorporated herein by reference. Background Technology

[0004] Due to the rapid growth in fossil fuel use, the demand for alternative or clean energy is increasing, and as part of this, the most active area of ​​research is in power generation and energy storage using electrochemical reactions.

[0005] Currently, secondary batteries are a representative example of electrochemical devices that utilize this type of electrochemical energy, and their designated applications tend to gradually expand.

[0006] With the technological advancements and increasing demands for mobile devices, the need for secondary batteries as an energy source has surged. Among these secondary batteries, lithium-ion batteries, characterized by high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. Furthermore, research is actively underway on methods for manufacturing high-density electrodes with even higher energy density per unit volume for use in such high-capacity lithium-ion batteries.

[0007] Typically, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and de-inserting lithium ions from the positive electrode, and silicon-based particles with high discharge capacity can be used as the negative electrode active material.

[0008] In particular, in response to the recent demand for high-density energy batteries, there is active research into combining silicon-based compounds (such as Si / C or SiO2) with graphite-based materials, which have 10 times or more capacity compared to graphite-based materials. x Silicon-based compounds, as high-capacity materials, offer the advantage of greater capacity compared to graphite used in related technologies. However, a drawback is that the battery's lifespan characteristics deteriorate during repeated charge and discharge processes due to significant volume expansion (~400%).

[0009] Therefore, to address the problems that arise when silicon-based compounds are used as anode active materials, methods for suppressing volume expansion itself (such as adjusting the driving potential, further coating the active material layer with a thin film, and adjusting the particle size of the silicon-based compound) or various methods for preventing the conductive path from being interrupted have been discussed. However, these methods can significantly degrade battery performance, and thus their application is limited, leaving constraints on the commercial manufacture of batteries that include anodes with high silicon-based compound content.

[0010] In particular, research is underway on the composition of binders based on volume expansion, and studies are being conducted to use binder polymers with strong stress on the sides to suppress the volume expansion of the negative electrode active material, which undergoes large volume changes during charging and discharging. However, these binder polymers alone have limitations in suppressing electrode thickness increases due to the shrinkage and expansion of the negative electrode active material, which leads to the degradation of lithium secondary battery performance.

[0011] Furthermore, to address the volume expansion problem of the negative electrode with silicon-based active materials as described above, an aqueous binder with dispersing and adhesive properties is used. While aqueous binders offer the advantage of improved dispersibility, their poor adhesion leads to problems such as electrode separation during the volume expansion of the active material.

[0012] Furthermore, when the electrode composition includes two types of electrode binders, depending on the type or amount of the electrode binder, the electrode binder cannot be used as both an electrode binder and an aggregate, which leads to problems such as reduced adhesion during electrode manufacturing, uneven coating, and pipe blockage.

[0013] In addition, rubber-based adhesives can be applied to improve adhesion. However, this application is known to have limitations because silicone-based active materials exhibit poor dispersibility when rubber-based adhesives are included.

[0014] Therefore, there is a need to study adhesives that do not disrupt the conductive network during the volume expansion of the active material and exhibit excellent adhesion even when manufacturing high-capacity batteries using high-capacity materials.

[0015] Reference List

[0016] (Patent Document 1) Korean Patent Application Publication No. 2022-0048854 Summary of the Invention

[0017] Technical issues

[0018] Therefore, the present invention aims to provide electrode compositions, electrode slurries, electrodes, and lithium secondary batteries, which include two types of electrode binders capable of preventing problems caused by volume changes in the negative electrode active material.

[0019] Another object of the present invention is to provide electrode compositions, electrode slurries, electrodes, and lithium secondary batteries comprising two types of electrode binders capable of preventing battery performance degradation caused by electrode binders added to suppress volume expansion of the negative electrode active material during charging and discharging.

[0020] Technical solution

[0021] An exemplary embodiment of the present invention provides an electrode composition comprising an electrode active material and an electrode binder, wherein the electrode composition is a positive electrode composition or a negative electrode composition, and the electrode binder comprises a first electrode binder and a second electrode binder, wherein the first electrode binder is an insoluble binder that is insoluble in an electrolyte solution, and the second electrode binder is a soluble binder that is soluble in the electrolyte solution, wherein the second electrode binder is an binder in which a polymer having an electrolyte solution affinity functional group or a modified electrolyte solution affinity functional group is attached to the first electrode binder, and the content of the second electrode binder relative to the electrode active material is 0.01 or greater.

[0022] Exemplary embodiments of the present invention provide an electrode slurry comprising an electrode composition and a solvent.

[0023] An exemplary embodiment of the present invention provides an electrode comprising an electrode current collector layer; and an electrode active material layer on one or both surfaces of the electrode current collector layer, the electrode active material layer comprising an electrode composition.

[0024] An exemplary embodiment of the present invention provides a lithium secondary battery, comprising: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein the first electrode or the second electrode is the aforementioned electrode.

[0025] Beneficial effects

[0026] When the second electrode binder dissolves in the electrolyte solution, the electrode composition according to an exemplary embodiment of the present invention can reduce resistance, improve output, and enhance the lifespan of the lithium secondary battery. Attached Figure Description

[0027] Figure 1 This is a schematic diagram illustrating an electrode comprising an electrode composition according to an exemplary embodiment of the present invention.

[0028] Figure 2 This is a schematic diagram illustrating an electrode comprising an electrode composition incorporating related technologies.

[0029] 10: Electrode active materials

[0030] 20: Electrode adhesive

[0031] 21: First electrode adhesive

[0032] 22: Second electrode adhesive Detailed Implementation

[0033] This instruction manual will be described in more detail below.

[0034] It should be understood that the terms or words used throughout the specification should not be construed as limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the invention, based on the inventor's ability to appropriately define the concepts of the words or terms in order to best explain the principles of the invention.

[0035] As used herein, singular terms (such as “a,” “an,” and “the”) are also intended to include plural forms unless the context clearly indicates otherwise.

[0036] In this specification, when a component is referred to as “comprising” a component, it means that the component may further include another component that does not exclude another component, unless explicitly stated otherwise.

[0037] Throughout this specification, when a component is referred to as "on another component," the component may be in direct contact with the other component, or there may be an intermediate component present.

[0038] In this specification, "p to q" means a range of "p or more and q or less".

[0039] As used herein, the description "a polymer comprising a particular monomer as a monomer unit" means that the monomer participates in the polymerization reaction and is included in the polymer as a repeating unit.

[0040] As used herein, when describing a polymer as including monomers, this is interpreted in the same way as when the polymer includes monomers as monomer units.

[0041] In this specification, it should be understood that, unless otherwise stated, the term 'polymer' is used in the broad sense to include copolymers.

[0042] In this specification, the "weight-average molecular weight (Mw)" and "number-average molecular weight (Mn)" of a compound can be determined using the compound's molecular weight and molecular weight distribution. Specifically, tetrahydrofuran (THF) and the compound are placed in a 1 ml glass vial to prepare a sample solution with a compound concentration of 1% by weight. A standard sample (polystyrene) and the sample solution are filtered through a filter (0.45 μm pore size) and injected into a GPC injector. The molecular weight and molecular weight distribution of the compound are determined by comparing the elution time of the sample solution with the calibration curve of the standard sample. In this case, an Infinity II 1260 (Agilent Co.) can be used as the measuring device, with the flow rate and column temperature set to 1.00 mL / min and 40.0 °C.

[0043] In this specification, unless otherwise specified, molecular weight refers to weight-average molecular weight.

[0044] In the following, exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings, enabling those skilled in the art to readily implement the invention. However, the present invention can be implemented in various different forms and is not limited to the following description.

[0045] <Electrode Composition>

[0046] An exemplary embodiment of the present invention provides an electrode composition comprising an electrode active material and an electrode binder, wherein the electrode composition is a positive electrode composition or a negative electrode composition, and the electrode binder comprises a first electrode binder and a second electrode binder, wherein the first electrode binder is an insoluble binder that is insoluble in an electrolyte solution, and the second electrode binder is a soluble binder that is soluble in the electrolyte solution, wherein the second electrode binder is an binder in which a polymer having an electrolyte solution affinity functional group or a modified electrolyte solution affinity functional group is attached to the first electrode binder, and the content of the second electrode binder relative to the electrode active material is 0.01 or greater.

[0047] The electrode composition according to the exemplary embodiment can remain as an electrode because the conductive network is maintained and the migration paths of electrons and ions are fixed.

[0048] The first electrode binder is an insoluble binder that is insoluble in the electrolyte solution and can be used to enhance the adhesion between electrode active material particles and between the electrode active material particles and the electrode current collector. The solubility of the first electrode binder in the electrolyte solution solvent can be 0.1% (w / w) or less in the temperature range of 25°C to 70°C.

[0049] The second electrode binder is a soluble binder dissolved in the electrolyte solution. When incorporated into the electrode, the binder forms adhesive forces to inhibit the separation of the electrode active material during the manufacturing process. In the presence of the electrolyte solution, the second electrode binder dissolves in the electrolyte solution, thereby forming pores at the locations where the second electrode binder is present. Therefore, pores are generated even in electrodes with low porosity, and the tortuosity of the electrolyte solution is increased. This reduces resistance and improves diffusion resistance, thereby extending lifetime and potentially increasing output. Furthermore, the diffusion effect of lithium ions allows the electrode to operate advantageously even during fast charging.

[0050] According to an exemplary embodiment of the present invention, the electrode composition may be a positive electrode composition, the electrode active material may be a positive electrode active material, and the mass ratio of the second electrode binder to the positive electrode active material may be 0.01 or higher and 0.02 or lower.

[0051] Preferably, the mass ratio of the second electrode binder to the positive electrode active material can be 0.01 or greater and less than 0.02, or 0.015 or less, or 0.012 or less.

[0052] In an exemplary embodiment, when the content of the second electrode binder relative to the positive electrode active material falls within the aforementioned range, it becomes more advantageous to form pores in the second electrode binder, and the electron migration path is maintained through the connection between the active material and the binder, thereby allowing the electrode to operate normally.

[0053] According to an exemplary embodiment of the present invention, the electrode composition may be a negative electrode composition, the electrode active material may be a negative electrode active material, and the mass ratio of the second electrode binder to the negative electrode active material may be 0.02 or greater.

[0054] Preferably, the mass ratio of the second electrode binder to the negative electrode active material can be 0.04 or less, or 0.03 or less, or 0.02 or greater.

[0055] In an exemplary embodiment, when the content of the second electrode adhesive relative to the negative electrode active material falls within the aforementioned range, it becomes more advantageous to form pores in the second electrode adhesive, and the electron migration path is maintained through the connection between the active material and the adhesive, thereby allowing the electrode to operate normally.

[0056] According to an exemplary embodiment of the present invention, both the first electrode binder and the second electrode binder can be dissolved in one or more common solvents. During electrode manufacturing, the solvent is used to mix the electrode binder and the electrode active material to form an electrode slurry. When the electrode slurry is applied to the electrode current collector layer and then dried to manufacture the electrode, the first electrode binder improves the adhesion between the electrode active material particles and between the electrode active material particles and the electrode current collector, and the second electrode binder dissolves in the electrolyte solution to form pores, thereby creating pores even in electrodes with low porosity. This increases the tortuosity of the electrolyte solution, which reduces resistance and improves diffusion resistance, thereby extending lifetime and potentially increasing output. Furthermore, the diffusion effect of lithium ions allows the electrode to operate advantageously even during fast charging.

[0057] According to an exemplary embodiment of the present invention, the solubility of the second electrode adhesive in the solvent of the electrolyte solution can be from 1% (w / w) to 100% (w / w) within a temperature range of 20°C to 70°C. When the above range is met, the porosity of the electrode can be improved as the second electrode adhesive dissolves in the electrolyte solution.

[0058] According to an exemplary embodiment of the present invention, the solubility of the first electrode adhesive and the second electrode adhesive in the solvent can be from 1% (w / w) to 50% (w / w) within a temperature range of 10°C to 70°C. When the above range is met, the first electrode adhesive and the second electrode adhesive are thoroughly mixed so that they can be uniformly distributed on the electrode during electrode manufacturing.

[0059] According to an exemplary embodiment of the present invention, the electrode composition may be a negative electrode composition, and the first electrode binder may include at least one selected from the group consisting of: fluoropolymers, styrene polymers, polyvinyl alcohol (PVA), polyacrylonitrile (PAN), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), and sulfonated EPDM.

[0060] Fluoropolymers can be polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), or fluororubber, but there are no particular restrictions, as long as they are insoluble polymers.

[0061] The styrene-based polymer can be styrene-butadiene rubber (SBR), but there are no particular restrictions, as long as it is an insoluble polymer.

[0062] According to an exemplary embodiment of the present invention, the electrode composition may be a positive electrode composition, and the first electrode binder may include at least one selected from the group consisting of: polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyphenylene ether (PPO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyimide (PI), polysulfone (PSU), polyethylene terephthalate / polycarbonate (PET / PC), and acrylonitrile-butadiene-styrene (ABS).

[0063] According to an exemplary embodiment of the present invention, the electrolyte solution affinity functional group may include at least one selected from the group consisting of hexafluoropropylene (HFP), polyethylene glycol (PEO), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl maleate (DEM), and various copolymers thereof.

[0064] The second negative electrode adhesive can specifically be polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PPO), styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PEO), styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PPO), styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PPO), styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PAN), or styrene-butadiene rubber-hexafluoropropylene copolymer (PVDF-co-PAN).

[0065] The electrode is a negative electrode composition, and when using conventional soluble adhesives such as polyvinyl alcohol (PVA)-based polymers, polyacrylic acid (PAA)-based polymers, polyethylene glycol (PEG)-based polymers, polyacrylonitrile (PAN)-based polymers, or polyacrylamide (PAM)-based polymers as the second electrode adhesive (second negative electrode adhesive), unlike when using a second negative electrode adhesive in the form of a copolymer of a polymer having electrolyte solution affinity functional groups or modified electrolyte solution affinity functional groups linked to the first negative electrode adhesive, when a conventional negative electrode composition includes two types of negative electrode adhesives, depending on the type or content of the negative electrode adhesive, the negative electrode adhesive may not be usable as a negative electrode adhesive or may aggregate, which may cause problems such as reduced adhesion, uneven coating, and pipe blockage during negative electrode manufacturing.

[0066] The electrode composition is a positive electrode composition, and when conventional soluble binders such as polymethyl methacrylate (PMMA)-based polymers or polyimide (PI)-based polymers are used as the second electrode binder (second positive electrode binder), it differs from when a second positive electrode binder in the form of a copolymer (copolymer) linked to the first electrode binder is used, depending on the type or content of the electrode binder. This can lead to problems such as reduced adhesion, uneven coating, and pipe blockage during electrode manufacturing.

[0067] The second electrode binder is formed in the form of a copolymer in which polymers having electrolyte solution affinity functional groups or modified electrolyte solution affinity functional groups are linked to the first electrode binder. This results in the first and second electrode binders having a common chain, and therefore they do not repel each other due to differences in polarity, but can be uniformly mixed like surfactants. Therefore, when using the first and second electrode binders according to the invention, problems such as reduced adhesion, uneven coating, and pipe blockage during electrode manufacturing can be reduced.

[0068] According to an exemplary embodiment of the present invention, the molar ratio of the first electrode binder to the second electrode binder may be 3:7 to 7:3, or 4:6 to 6:4, and preferably 5:5. When the above ranges are met, the electrode composition may have improved water dispersibility and further improved lifetime performance.

[0069] Based on a total of 100 parts by weight of the first electrode adhesive and the second electrode adhesive, the content of the first electrode adhesive can be from 30 parts by weight to 90 parts by weight, and preferably can be 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, 45 parts by weight or more, or 50 parts by weight or more, and 85 parts by weight or less, 80 parts by weight or less, 75 parts by weight or less, 70 parts by weight or less, 65 parts by weight or less, or 60 parts by weight or less. When the above ranges are met, electrode collapse that may occur when the second electrode adhesive dissolves can be prevented, and pores generated when the second electrode adhesive dissolves can be maintained.

[0070] According to an exemplary embodiment of the present invention, based on a total of 100 parts by weight of the first electrode adhesive and the second electrode adhesive, the content of the second electrode adhesive can be from 10 parts by weight to 70 parts by weight, and preferably can be 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, and 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, 50 parts by weight or less, 45 parts by weight or less, or 40 parts by weight or less. When the above ranges are met, the pores generated when the second electrode adhesive dissolves can provide advantageous effects in terms of battery resistance, lifespan, output, etc.

[0071] According to an exemplary embodiment of the present invention, the weight-average molecular weight of the first electrode binder may be 100,000 g / mol or greater and 1,500,000 g / mol or less. The weight-average molecular weight of the second electrode binder may be 50,000 g / mol or greater and 3,000,000 g / mol or less. When the weight-average molecular weight of the electrode binder falls within the above-mentioned range, the electrode binder exhibits excellent mechanical strength and high intermolecular interactions, resulting in excellent adhesion of the electrode. Furthermore, when the above-mentioned range is met, the viscosity of the electrode binder can be set within an appropriate range, thereby obtaining excellent electrode coatability when using it to manufacture electrodes.

[0072] The electrode binder can be a negative electrode binder.

[0073] The electrode binder can be a positive electrode binder.

[0074] Electrode adhesives can be water-based adhesives.

[0075] When aqueous binders are used in electrode compositions, rapid dissolution, easy processability, and high efficiency can be achieved. The viscosity of the electrode slurry can be stably controlled in the future, long-term cycling can be achieved, and additional advantages such as high adhesion under a variety of operating temperature conditions can be provided.

[0076] For the manufacture of water-based adhesives, polymerization initiators are used, and examples of polymerization initiators may include, but are not limited to, ammonium persulfate.

[0077] According to an exemplary embodiment of the present invention, the electrolyte solution may include, but is not limited to, one or more solvents selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).

[0078] The electrolyte solution may include, but is not limited to, one or more solvents selected from, for example, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), butyl carbonate (BC), γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, trimethoxymethane, dioxolane derivatives, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0079] In particular, among carbonate organic solvents, ethylene carbonate and propylene carbonate (which are cyclic carbonates) are high-viscosity organic solvents and can be preferably used because they have high dielectric constants to effectively dissociate lithium salts. When cyclic carbonates are mixed and used with straight-chain carbonates (such as dimethyl carbonate and diethyl carbonate) having low viscosity and low dielectric constants in appropriate proportions, electrolytes with high conductivity can be prepared, and therefore can be used more preferably.

[0080] The electrode active material can be a negative electrode active material.

[0081] According to an exemplary embodiment of the present invention, the electrode active material may include one or more selected from the group consisting of silicon-based active materials and carbon-based active materials.

[0082] Based on the solid content of 100 parts by weight of the electrode composition, the content of the electrode active material may be 90 parts by weight or more and 99 parts by weight or less, preferably 92 parts by weight or more, or 95 parts by weight or more, and 98.5 parts by weight or less, or 98 parts by weight or less.

[0083] According to an exemplary embodiment of the present invention, the silicon-based active material may include materials selected from Si and SiO2. xone or more selected from the group consisting of (0<x<2), Si / C, and Si alloys. The silicon-based active material has a capacity at least 10 times higher than that of the carbon-based active material, and therefore, when the silicon-based active material is applied to an electrode, particularly a negative electrode, an electrode with a high level of energy density can be achieved even with a reduced thickness, compared to the case where the carbon-based active material is included alone.

[0084] The electrode active material may include a silicon-based active material, and the silicon-based active material may include a member selected from the group consisting of Si and SiO x (0<x<2), one or more thereof.

[0085] The silicon-based active material may use only pure silicon (Si) as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on 100 parts by weight of the total silicon-based active material as described above, pure Si particles that are not bound to other particles or elements are included in the above range.

[0086] The electrode composition including the silicon-based active material within the above content range is meaningful because, despite the large amount of the silicon-based active material, the amount of hydrogen gas generated by the silicon-based active material is significantly reduced by controlling the pH of the binder.

[0087] The silicon-based active material may exist in a crystalline form or an amorphous form. Specifically, the silicon particles of the silicon-based active material may preferably be spherical particles, but are not limited thereto.

[0088] In SiO x , SiO₂ where x is 2 is not included, because SiO₂ does not react with lithium ions and thus cannot store lithium. Therefore, x is preferably within the above range of the exemplary embodiments.

[0089] In the present specification, the silicon-based active material may be Si / C composed of a composite material of Si and C. For example, each peak of Si and C can be observed by an elemental analysis method such as XRD or NMR. The silicon-carbon composite material, which may be expressed as Si / C, may consist of Si and C that are not bonded to each other, but may also include additional components as needed. For example, the silicon-carbon composite material may or may not include silicon carbide represented as SiC. When the silicon-carbon composite material contains silicon carbide, its content is 3 wt% or less. The silicon-carbon composite material may exist in a crystalline state, an amorphous state, or a mixed state thereof. According to an example, C in the silicon-carbon composite material may exist in an amorphous state.

[0090] According to an exemplary embodiment of the present invention, the carbon-based active material may include one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.

[0091] When the electrode active material is composed of silicon-based and carbon-based active materials, the composition ratio between the silicon-based and carbon-based active materials can be in the range of 2:98 to 30:70. Electrode active materials that meet the above range mainly include carbon-based active materials as the main component, and therefore exhibit small volume expansion during charging and discharging, resulting in reduced expansion and the additional effect of excellent conductive connectivity of the electrode.

[0092] The electrode active material can be a positive electrode active material.

[0093] The positive electrode active material can be a commonly used positive electrode active material. Specifically, the positive electrode active material can be a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; lithium iron oxide, such as LiFe3O4; or a compound with the chemical formula Li 1+c1 Mn 2-c1 Lithium manganese oxides represented by O4 (0≤c1≤0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxides (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5, and Cu2V2O7; and those represented by the chemical formula LiNi 1-c2 M c2 O2 (where M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01 ≤ c2 ≤ 0.3) represents a Ni-site type lithium nickel oxide; LiMn 2-c3 M c3 Lithium manganese composite oxides represented by O2 (where M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (where M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, wherein a portion of the Li in the chemical formula is replaced by alkaline earth metal ions, etc., but not limited thereto.

[0094] According to an exemplary embodiment of the present invention, the electrode composition may include an electrode conductive material, and based on 100 parts by weight of the electrode composition, the content of the electrode conductive material may be 0.03 parts by weight or more and 40 parts by weight or less. Specifically, based on 100 parts by weight of the electrode composition, the content of the conductive material may be 0.03 parts by weight or more and 40 parts by weight or less, preferably 0.05 parts by weight or more and 30 parts by weight or less, more preferably 0.5 parts by weight or more and 25 parts by weight or less.

[0095] According to an exemplary embodiment of the present invention, the electrode composition may include an electrode conductive material, and the electrode conductive material may include one or more selected from the group consisting of point conductive materials, planar conductive materials, and linear conductive materials.

[0096] Electrode conductive materials can include dot-shaped conductive materials and linear conductive materials.

[0097] Dot-shaped conductive materials refer to dot-shaped or spherical conductive materials that can be used to improve the conductivity of electrodes and are conductive without causing chemical changes. Specifically, dot-shaped conductive materials can be at least one selected from the group consisting of: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fibers, fluorocarbons, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium dioxide, and polyphenylene derivatives, and preferably include carbon black and / or artificial graphite for achieving high conductivity and excellent dispersibility.

[0098] Planar conductive materials can improve conductivity by increasing the planar contact between silicon particles in the electrode, while simultaneously suppressing the interruption of conductive paths due to volume expansion. Planar conductive materials can be represented as plate-shaped conductive materials or bulk-shaped conductive materials. Examples of planar conductive materials may include at least one selected from the group consisting of plate-shaped graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-shaped graphite.

[0099] Linearly conductive materials can be carbon nanotubes. Carbon nanotubes can be bundled carbon nanotubes. Bundled carbon nanotubes can comprise multiple carbon nanotube units. Specifically, unless otherwise stated, the term "bundle-type" herein refers to a bundle-shaped or rope-shaped secondary shape in which multiple carbon nanotube units are aligned or wound side-by-side in an orientation in which the longitudinal axes of the carbon nanotube units are substantially the same. The carbon nanotube units are cylindrical graphite sheets with nanometer-sized diameters and have sp... 2 Bonded structure. In this case, depending on the rolling angle and structure of the graphite sheet, it can exhibit properties of a conductive or semiconductor material. Compared to entangled type carbon nanotubes, bundled carbon nanotubes can be more uniformly dispersed during the fabrication of the negative electrode and can more smoothly form a conductive network in the negative electrode to improve its conductivity.

[0100] The electrode conductive material can be a negative electrode conductive material.

[0101] The electrode conductive material can be a positive electrode conductive material.

[0102] The negative conductive material is applied to the negative electrode and is configured to be completely separate from the positive conductive material applied to the positive electrode. That is, the negative conductive material is used to support the contact point between the silicon-based active materials, which undergoes large volume expansion of the electrode due to charging and discharging, while the positive conductive material is used to impart partial conductivity and also acts as a buffer material during winding. Therefore, the construction and function of the negative and positive conductive materials are different from each other.

[0103] Positive electrode conductive materials are used to impart conductivity to the electrodes and can be used without specific limitations, as long as they are electronically conductive without causing chemical changes in the battery to be configured. Specific examples may include: graphite, such as natural and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more of them may be used.

[0104] According to an exemplary embodiment of the present invention, the electrode composition may further include a thickener, the type and amount of which are not particularly limited, and carboxymethyl cellulose (CMC) can be used as a thickener, for example.

[0105] <Method for Manufacturing Electrode Compositions>

[0106] The electrode composition of the present invention can be manufactured by the following steps: preparing an electrode active material; preparing a first electrode binder; preparing a second electrode binder; and adding an electrode conductive material. In this specification, the above description can be applied to electrode active materials, the first electrode binder, the second electrode binder, and conductive materials, etc.

[0107] <Electrode Paste>

[0108] The electrode slurry according to an exemplary embodiment of the present invention comprises the above-described electrode composition and a solvent.

[0109] Solvents may include those known in the art. For example, solvents may be water (e.g., distilled water) or N-methyl-2-pyrrolidone (NMP), but are not limited thereto.

[0110] The electrode paste can be a negative electrode paste, therefore the electrode composition can be used as a negative electrode paste.

[0111] The electrode slurry can be a positive electrode slurry, therefore the electrode composition can be used as a positive electrode slurry.

[0112] In some cases, by appropriately adjusting the average particle size (D) of the silicon-based active material 50By appropriately adjusting the specific surface area of ​​the silicon-based active material to control the viscosity of the electrode paste within an appropriate range, the dispersion of components (e.g., conductive materials, binders, silicon-based active materials, and carbon-based active materials) in the electrode paste can be improved. Therefore, the contact area between components can be improved, allowing the conductive network to be maintained, increasing capacity retention, and preventing non-uniformity of current density during charging and discharging.

[0113] In addition, in some cases, the viscosity of the electrode paste can be adjusted to 5000 cps to 20000 cps. When the viscosity falls within the above range, it exhibits excellent storage stability and excellent coatability when the electrode paste is to be coated on one or both surfaces of the electrode current collector layer in the future.

[0114] <Electrode>

[0115] An electrode according to an exemplary embodiment of the present invention includes an electrode current collector layer; and an electrode active material layer on one or both surfaces of the electrode current collector layer, the electrode active material layer comprising the above-described electrode composition.

[0116] The electrode can be the negative electrode; therefore, the electrode current collector layer, electrode slurry, and electrode active material layer are all used as the negative electrode.

[0117] The negative electrode current collector layer typically has a thickness of 1 μm to 100 μm. There are no particular limitations on this layer, as long as it possesses high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys can be used. Furthermore, the negative electrode current collector layer can have microscopic irregularities formed on its surface to enhance the adhesion of the negative electrode active material, and it can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.

[0118] This invention provides a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode current collector layer is 1 μm or greater and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or greater and 500 μm or less. However, the thickness can be modified differently depending on the type and application of the negative electrode used, and is not limited thereto.

[0119] The electrode can be a positive electrode; therefore, the electrode current collector layer, electrode slurry, and electrode active material layer are all used for the positive electrode.

[0120] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including positive electrode active material.

[0121] In the positive electrode, there are no particular restrictions on the current collector, as long as it is conductive and will not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, and aluminum or stainless steel that have been surface-treated with carbon, nickel, titanium, silver, etc., can be used. Furthermore, the positive electrode current collector can typically have a thickness from 3 μm to 500 μm, and its surface can have microscopic irregularities to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0122] The positive electrode can be Li metal.

[0123] The positive electrode active material layer may include a positive electrode conductive material, a positive electrode binder, and the aforementioned positive electrode active material.

[0124] <Lithium secondary batteries>

[0125] An exemplary embodiment of the present invention provides a lithium secondary battery, which includes a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein the first electrode or the second electrode is the aforementioned electrode.

[0126] Specifically, the first electrode can be a negative electrode and the second electrode can be a positive electrode, or the first electrode can be a positive electrode and the second electrode can be a negative electrode.

[0127] Specifically, a lithium secondary battery may include a negative electrode, a positive electrode, a separator inserted between the positive and negative electrodes, and an electrolyte, wherein the negative electrode is the same as described above. Since the negative electrode has already been described above, its detailed description is omitted.

[0128] The separator is used to separate the negative and positive electrodes and provide a migration path for lithium ions. Any separator can be used without particular limitation, as long as it is typically used in secondary batteries. In particular, separators with high moisture retention capacity for the electrolyte and low resistance to the migration of electrolyte ions are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes made of polyolefin-based polymers, such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or stacked structures having two or more of these layers. Furthermore, commonly used porous nonwoven fabrics can be used, such as nonwoven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Additionally, separators coated with ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and separators with single-layer or multi-layer structures can be selectively used.

[0129] Examples of electrolytes may include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes, which can be used in the manufacture of lithium secondary batteries.

[0130] Specifically, electrolytes may include metal salts.

[0131] Lithium salts can be used as metal salts, and they are readily soluble in non-aqueous electrolytes, such as those selected from F. - Cl - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - One or more of the groups can be used as anions of lithium salts.

[0132] In addition to the electrolyte components mentioned above, one or more additives, such as alkyl halogenated carbonate compounds (e.g., ethylene difluorocarbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether (glyme), triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinanes, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum trichloride, may be further included in the electrolyte to improve battery life characteristics, suppress battery capacity reduction, and increase battery discharge capacity.

[0133] Exemplary embodiments of the present invention provide a battery module including a lithium secondary battery as a battery cell and a battery pack including the battery module. Optionally, a battery pack including a lithium secondary battery is provided. Since the battery module and battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and battery pack can be used as a power source for medium to large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and energy storage systems.

[0134] Figure 1 This is a schematic diagram illustrating an electrode comprising an electrode composition according to an exemplary embodiment of the present invention, and Figure 2 This is a schematic diagram illustrating an electrode comprising an electrode composition incorporating related technologies. According to... Figure 1 It can be confirmed that when the first electrode binder and the second electrode binder are used and introduced into the electrolyte solution, the effects of reduced resistance, improved output, and increased lifespan are achieved. However, according to Figure 2 It can be confirmed that when a certain type of adhesive is used and introduced into the electrolyte solution, no effect of reduced resistance, improved output, or increased lifespan is obtained.

[0135] Implementation of the invention

[0136] Preferred embodiments will be provided below to better understand the invention. It will be apparent to those skilled in the art that the embodiments are provided merely for illustrative purposes, and various modifications and alterations can be made within the scope and spirit of the invention. Such modifications and alterations naturally fall within the scope of the claims included herein.

[0137] <Preparation Example 1: Preparation of Negative Electrode Binder>

[0138] Preparation Example 1-1

[0139] In a reactor equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet pipe, a first negative electrode binder (styrene-butadiene rubber (SBR)) was prepared at a content of 2.3%, and a second negative electrode binder (styrene-butadiene rubber-hexafluoropropylene copolymer (SBR-co-HFP)) was prepared at a content of 2%. Subsequently, the binders were dissolved in distilled water at room temperature and mixed in a binder mixing reactor to prepare the negative electrode binder.

[0140] Preparation Examples 1-2

[0141] In a reactor equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet pipe, a first negative electrode binder (polyvinylidene fluoride (PVDF)) was prepared at a content of 2.3%, and a second negative electrode binder (PVDF-co-HFP) was prepared at a content of 2%. Subsequently, the binders were dissolved in N-methyl-2-pyrrolidone (NMP) at room temperature and mixed in a binder mixing reactor to prepare the negative electrode binder.

[0142] Comparative Preparation Example 1-1

[0143] In a reactor equipped with a stirrer, thermometer, reflux condenser and nitrogen inlet pipe, a first negative electrode binder (styrene-butadiene rubber (SBR)) was prepared at a content of 4.3%, and then dissolved in distilled water at room temperature and mixed in a binder mixing reactor to prepare the negative electrode binder.

[0144] <Preparation Example 2: Preparation of Positive Electrode Binder>

[0145] Preparation Example 2-1

[0146] In a reactor equipped with a stirrer, thermometer, reflux condenser and nitrogen inlet pipe, a first positive electrode binder (which is polyvinylidene fluoride (PVDF)) was prepared at a content of 1%, and a second positive electrode binder (which is polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP)) was prepared at a content of 1%. The binders were then mixed at room temperature in the presence of N-methyl-2-pyrrolidone (NMP) to prepare the positive electrode binder.

[0147] Preparation Example 2-2

[0148] The positive electrode binder was prepared in the same manner as in Preparation Example 2-1, except that: the first positive electrode binder (which is polyvinyl chloride (PVC)) was prepared at a content of 1%, and the second positive electrode binder (which is polyvinyl chloride-hexafluoropropylene copolymer (PVC-co-HFP)) was prepared at a content of 1%, and then the binders were mixed in the presence of tetrahydrofuran (THF).

[0149] <Example 1: Preparation of the negative electrode composition>

[0150] Prepare various negative electrode compositions having the composition and content (based on % (w / w)) of Table 1 below.

[0151] [Table 1]

[0152]

[0153] <Example 2: Preparation of the positive electrode composition>

[0154] Prepare various cathode compositions having the composition and content (based on % (w / w)) shown in Table 2 below.

[0155] [Table 2]

[0156]

[0157] <Preparation Example: Preparation of Electrodes and Lithium Secondary Batteries>

[0158] Example 3-1: Preparation of negative electrode and lithium secondary battery

[0159] A negative electrode slurry was prepared by adding a negative electrode composition having the composition of Examples 1-1 in Table 1 to distilled water, which was used as a solvent to form the negative electrode slurry. Subsequently, a layer of the negative electrode active material was applied to an 8 μm thick Cu foil at a concentration of 76.34 mg / 25 cm⁻¹. 2 The negative electrode loading was coated to a thickness of 38 μm, then dried at 130 °C for 12 hours and rolled to prepare the negative electrode. Lithium metal was used as the positive electrode, a polyolefin separator was inserted between the negative electrode and the lithium metal, and an electrolyte including 1M LiPF6 dissolved in a solvent was injected. Ethyl carbonate (EC) and diethyl carbonate (DEC) were mixed in the solvent at a volume ratio of 30:70 to prepare a lithium secondary battery.

[0160] Example 3-2: Preparation of negative electrode and lithium secondary battery

[0161] The negative electrode and lithium secondary battery were prepared in the same manner as in Example 3-1, except that the negative electrode composition having the composition of Examples 1-2 in Table 1 was added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming the negative electrode slurry to prepare the negative electrode slurry.

[0162] Comparative Example 3-1: Preparation of Anode and Lithium Secondary Battery

[0163] The negative electrode and lithium secondary battery were prepared in the same manner as in Example 3-1, except that a negative electrode composition having the composition of Comparative Example 1-1 in Table 1 was added to prepare a negative electrode slurry.

[0164] Example 4-1: Preparation of the positive electrode and lithium secondary battery

[0165] A positive electrode slurry was prepared by adding a positive electrode composition having the composition of Examples 2-1 in Table 2 to N-methyl-2-pyrrolidone (NMP), which was used as a solvent to form the positive electrode slurry. Subsequently, a solution of 537 mg / 25 cm⁻¹ was applied to both surfaces of an aluminum current collector (thickness: 12 μm) used as the positive electrode current collector. 2The positive electrode slurry was coated with a loading amount of material, then rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thus preparing the positive electrode. A Si negative electrode was used as the positive electrode, a polyolefin separator was inserted between the negative and positive electrodes, and an electrolyte containing 1M LiPF6 dissolved in a solvent was injected. Ethyl carbonate (EC) and diethyl carbonate (DEC) were mixed in the solvent at a volume ratio of 30:70 to prepare a lithium secondary battery.

[0166] Example 4-2: Preparation of the positive electrode and lithium secondary battery

[0167] The positive electrode and lithium secondary battery were prepared in the same manner as in Example 4-1, except that the positive electrode composition having the composition of Example 2-2 in Table 2 was added to tetrahydrofuran (THF:Tetrahydrofuran) as a solvent to form the positive electrode slurry to prepare the positive electrode slurry.

[0168] <Experimental Example: Evaluation of Battery Characteristics>

[0169] Experimental Example 1: Initial Capacity Efficiency and Energy Efficiency

[0170] The lifetime and capacity retention of the prepared lithium secondary batteries were evaluated using an electrochemical charge / discharge tester. The lithium secondary batteries were tested for three cycles under conditions of 4.2–2.5 V and 0.3 C / 0.3 C, and the charging capacity and energy, as well as the discharging capacity and energy, of the third cycle were measured to evaluate efficiency. The results are shown in Table 3 below.

[0171] Experiment Example 2: Resistance

[0172] The SOC was set to 50%, and pulses of 0.3 C, 0.5 C, 1 C, and 1.5 C were applied for 10 seconds each in the charging and discharging directions. The average DC internal resistance (DCIR) was derived to evaluate the resistance. The results are shown in Table 3.

[0173] Experiment Example 3: Charging Output

[0174] The prepared lithium secondary battery was charged at 2.5 C in the charging direction at 25 °C and 80% SOC until the voltage reached 4.3 V, and the time required to reach the end of charging was measured to evaluate the charging output. The results are shown in Table 3 below.

[0175] [Table 3]

[0176]

[0177] According to Table 3, in Example 3-1, a first negative electrode adhesive of styrene-butadiene rubber (SBR) and a second negative electrode adhesive of styrene-butadiene rubber-hexafluoropropylene copolymer (SBR-co-HFP) were used; in Example 3-2, a first negative electrode adhesive of polyvinylidene fluoride (PVDF) and a second negative electrode adhesive of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP) were used; in Example 4-1, a first positive electrode adhesive of polyvinylidene fluoride (PVDF) and a second positive electrode adhesive of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP) were used; and in Example 4-2, a first positive electrode adhesive of polyvinyl chloride (PVC) and a second positive electrode adhesive of polyvinyl chloride-hexafluoropropylene copolymer (PVC-co-HFP) were used. Since the first and second electrode adhesives share a common chain, they do not repel each other due to differences in polarity, but can be uniformly mixed like surfactants. When the second electrode binder dissolves in the electrolyte solution, pores are formed in the areas where the second electrode binder already exists, thus creating pores even in electrodes with low porosity. As a result, the tortuosity of the electrolyte solution is increased, resistance is reduced, diffusion resistance is improved, lifetime is extended, and output is increased.

[0178] In contrast, in Comparative Example 3-1, no pores were formed because no second negative electrode adhesive was used, and the resistance was higher than that of the Example, and the output was lower than that of the Example.

Claims

1. An electrode composition comprising: Electrode active materials; and Electrode adhesive, in which The electrode composition is either a positive electrode composition or a negative electrode composition. The electrode adhesive includes a first electrode adhesive and a second electrode adhesive. The first electrode adhesive is an insoluble adhesive that is insoluble in electrolyte solutions. The second electrode adhesive is a soluble adhesive that dissolves in the electrolyte solution. The second electrode binder is an electrode binder in which a polymer having electrolyte solution affinity functional groups or modified electrolyte solution affinity functional groups is linked to the first electrode binder, and The content of the second electrode binder relative to the electrode active material is 0.01 or greater.

2. The electrode composition according to claim 1, wherein, The electrode composition is a positive electrode composition. The electrode active material is a positive electrode active material, and The mass ratio of the second electrode binder to the positive electrode active material is 0.01 or greater and 0.02 or less.

3. The electrode composition according to claim 1, wherein, The electrode composition is a negative electrode composition. The electrode active material is a negative electrode active material, and The mass ratio of the second electrode binder to the negative electrode active material is 0.02 or greater.

4. The electrode composition according to claim 1, wherein, Both the first electrode adhesive and the second electrode adhesive are dissolved in one or more common solvents.

5. The electrode composition according to claim 1, wherein, The solubility of the second electrode adhesive in the solvent of the electrolyte solution is 1% (w / w) to 100% (w / w) in the temperature range of 20°C to 70°C.

6. The electrode composition according to claim 5, wherein, The solubility of the first electrode adhesive and the second electrode adhesive in the solvent is 1% (w / w) to 50% (w / w) in the temperature range of 10°C to 70°C.

7. The electrode composition according to claim 1, wherein, The electrode composition is a negative electrode composition, and The first electrode adhesive comprises at least one selected from the group consisting of: fluoropolymers, styrene polymers, polyvinyl alcohol (PVA), polyacrylonitrile (PAN), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), and sulfonated EPDM.

8. The electrode composition according to claim 1, wherein, The electrode composition is a positive electrode composition, and The first electrode adhesive comprises at least one selected from the group consisting of: polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyphenylene ether (PPO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyimide (PI), polysulfone (PSU), polyethylene terephthalate / polycarbonate (PET / PC), and acrylonitrile-butadiene-styrene (ABS).

9. The electrode composition according to claim 1, wherein, The electrolyte solution affinity functional group includes at least one selected from the group consisting of hexafluoropropylene (HFP), polyethylene glycol (PEO), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl maleate (DEM), and various copolymers thereof.

10. The electrode composition according to claim 1, wherein, The electrolyte solution includes one or more solvents selected from the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).

11. The electrode composition according to claim 1, wherein, Based on the solids content of 100 parts by weight of the electrode composition, the total amount of the first electrode binder and the second electrode binder is 0.5 parts by weight or more and 30 parts by weight or less.

12. The electrode composition according to claim 1, wherein, Based on the total amount of 100 parts by weight of the first electrode adhesive and the second electrode adhesive, the content of the second electrode adhesive is from 10 parts by weight to 70 parts by weight.

13. The electrode composition according to claim 1, wherein, The weight-average molecular weight of the first electrode binder is 100,000 g / mol or greater and 1,500,000 g / mol or less.

14. The electrode composition according to claim 1, wherein, The electrode active material includes one or more selected from the group consisting of silicon-based active materials and carbon-based active materials.

15. The electrode composition according to claim 14, wherein, The silicon-based active material includes one or more selected from the group consisting of: Si, SiO x (0<x<2), Si / C, and Si alloy.

16. The electrode composition according to claim 14, wherein, The carbon-based active material includes one or more selected from the group consisting of: artificial graphite, natural graphite, hard carbon, and soft carbon.

17. The electrode composition according to claim 1, wherein, The electrode composition includes an electrode conductive material, and the electrode conductive material is included in an amount of 0.03 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the electrode composition.

18. The electrode composition according to claim 1, wherein, The electrode composition includes an electrode conductive material, and the electrode conductive material includes one or more selected from the group consisting of: point conductive materials, planar conductive materials, and linear conductive materials.

19. An electrode paste, comprising: The electrode composition according to any one of claims 1 to 18, and Solvent.

20. An electrode comprising: Electrode current collector layer; and An electrode active material layer on one or both surfaces of the electrode current collector layer, the electrode active material layer comprising the electrode composition according to any one of claims 1 to 18.

21. A lithium secondary battery, comprising: First electrode; Second electrode; A partition plate disposed between the first electrode and the second electrode; as well as Electrolytes, The first electrode or the second electrode is the electrode according to claim 20.

22. A battery module comprising the lithium secondary battery according to claim 21.

23. A battery pack comprising the lithium secondary battery according to claim 21.

24. A battery pack comprising the battery module according to claim 22.

Citation Information

Patent Citations

  • Method for detecting subscriber identity module swap attack and apparatus thereof

    KR1020240147180A

  • Positive electrode active material for rechargeable lithium battery, method for manufacturing the same, and rechargeable lithium battery including the same

    KR1020250155274A